The genus Brachyptera Newport (Plecoptera: Taeniopterygidae) in the Peloponnes, Greece - Murányi, Dávid (Zootaxa, 2011)
A new species of the genus Brachyptera (Plecoptera: Taeniopterygidae), B. kontschani sp. n. is described on the basis of a male and eight female adults collected in the Peloponnes, Greece. Remarks on the closely related and poorly known B. dinarica Aubert, and notes on the distribution and ecology of the Brachyptera species known from the Peloponnes are also presented.